Comparison of five-day Helicobacter pylori eradication regimens: rabeprazole-based and omeprazole-based regimens with and without omeprazole pretreatment - Adachi, Kyoichi (Elsevier, 2003)
Background: The onset of antisecretory activity of rabeprazole is faster than that of omeprazole. Objective: This study was performed to compare the efficacy of short-term rabeprazole-based triple therapy with that of omeprazole-based triple therapy and to determine the influence of omeprazole pretreatment in omeprazole-based short-term triple therapy. Methods: This was a 2-center, open-label, prospective, randomized study. Patients who tested positive for Helicobacter (formerly Campylobacter) pylori were randomized to one of three 5-day regimens: (1) rabeprazole 20 mg BID, amoxicillin 500 mg TID, and clarithromycin 400 mg BID (RAC group); (2) omeprazole 20 mg BID, amoxicillin 500 mg TID, and clarithromycin 400 mg BID without omeprazole pretreatment (OAC1 group); and (3) omeprazole 20 mg BID, amoxicillin 500 mg TID, and clarithromycin 400 mg BID with 5 days of omeprazole pretreatment 20 mg BID (OAC2 group). Eradication was assessed by (13)C-urea breath test and rapid urease test ∼1 month after completion of treatment. All patients who entered this study were included in the intent-to-treat (ITT) analysis, patients who completed the study were included in the per-protocol (PP) analysis, and patients who did not undergo the (13)C-urea breath test and rapid urease test were included in the all-patients-treated (APT) analysis. Results: A total of 120 patients (86 men, 34 women; mean [SD] age, 55.8 [14.3] years; range, 19–86 years) were assigned to the RAC, OAC1, or OAC2 group (40 patients in each group). ITT, PP, and APT eradication rates in the RAC group were 90%, 92%, and 90%, respectively; in the OAC1 group, 75%, 83%, and 75%; and in the OAC2 group, 85%, 90%, and 87%. These eradication rates were not significantly different between groups. Conclusions: Eradication rates did not differ significantly between the three 5-day proton pump inhibitor–based triple therapies in this study population. However, 5-day rabeprazole-based triple therapy tends to be more effective than 5-day omeprazole-based triple therapy in the eradication of H pylori, and treatment with omeprazole before eradication therapy may improve the eradication rates of 5-day omeprazole-based therapy.